Gut instincts : a clinician's handbook of digestive and liver diseases - Esrailian, Eric (SLACK Incorporated, 2012)
"Gut Instincts: A Clinician's Handbook of Digestive and Liver Diseases is a practical handbook that focuses on the diagnosis and management of the most commonly encountered digestive diseases."--Page 4 of cover.